Characterization of a Paramagnetic Mononuclear Nonheme Iron-Superoxo Complex - Chiang, Chien-Wei (American Chemical Society, 2014)
[Image: see text] O(2) bubbling into a THF solution of Fe(II)(BDPP) (1) at −80 °C generates a reversible bright yellow adduct 2. Characterization by resonance Raman and Mössbauer spectroscopy provides complementary insights into the nature of 2. The former shows a resonance-enhanced vibration at 1125 cm(–1), which can be assigned to the ν(O–O) of a bound superoxide, while the latter reveals the presence of a high-spin iron(III) center that is exchange-coupled to the superoxo ligand, like the Fe(III)–O(2)(–) pair found for the O(2) adduct of 4-nitrocatechol-bound homoprotocatechuate 2,3-dioxygenase. Lastly, 2 oxidizes dihydroanthracene to anthracene, supporting the notion that Fe(III)–O(2)(–) species can carry out H atom abstraction from a C–H bond to initiate the 4-electron oxidation of substrates proposed for some nonheme iron enzymes.